HUBUNGAN KEPERCAYAAN DIRI TERHADAP PERILAKU MENCONTEK PADA SISWA DI SMP NEGERI 2 GEMPOL - Pravita Dwi Cahyani; Eko Hardi Ansyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Cheating behavior is an act that someone does to get maximum results by ignoring applicable rules and can have a lasting impact on the order of life and this behavior is one of the causes of a person's lack of confidence in the abilities they have. So this study aims to determine the relationship between self-confidence and students' cheating behavior at SMP X. This study uses a quantitative method with the subject of students of SMP X. In this study, a sample of 217 students of SMP X was used which was obtained from the saturated sample technique. Data collection techniques were carried out using a self-confidence scale and a cheating behavior scale with variable measurements using a Likert scale. Data were analyzed by testing the hypothesis using Pearson's Correlations with the help of Windows JASP 16.3. The results of the analysis obtained are r = 0.238 <0.05 and p = <0.001 so that the hypothesis is accepted and there is a significant relationship, meaning that there is a relationship between self-confidence and cheating behavior. This study also found a negative relationship and an adjusted R square value of 0.065 or 7%, which means that the effect of self-confidence and cheating behavior has a very low level of relationship.